Биомасса и энергетическая характеристика лесной почвенной мезофауны немелиорированных земель Белорусского Полесья - Савицкий, Б.П.; Веремеев, В.Н. (Вестник зоологии, 1980)
Amount, biomass and energy characteristic of the soil mesofauna in the Byelorussian Polessian forests (within the formation bounderies) which were not subjected to drainage reclamation are determined by the subsoil water level and decrease regularly with the subsoil water level. This fact should be taken into account when planning and carrying out drainage reclamation of forest areas.